Analisis kesulitan belajar daring pada mata pelajaran biologi siswa kelas XI SMAN 2 Mandau tahun ajaran 2021/2022 - Prida Juniarti; Mellisa Mellisa (Bio-Pedagogi : Jurnal Pembelajaran Biologi, 2023)
ENThis study aims to determine the difficulties of online learning in class XI Biology students at SMAN 2 Mandau. This research was conducted in January-March 2022. The implementation of this research used a quantitative descriptive method with survey techniques. The sampling technique used a random sampling technique (simple random sampling). The number of research samples is 122 students. The instrument used was an online learning difficulties questionnaire which consisted of 30 statement items and had been validated. The data collection technique in this study used a questionnaire which was distributed directly in the class. Based on the research, it is known that the factors causing online learning difficulties in biology class XI students are the first indicator of signal technical constraints and online learning disabilities in the high category of 70.76%, the second indicator of the implementation of interactions, assignments and teaching materials in online learning is 67.33% in the high category , the third indicator of stakeholders helping the government, schools, parents of students in online learning is 69.55% in the high category. Based on the results of data processing and analysis, it can be concluded that the online learning difficulties of class XI Biology students at SMAN 2 Mandau for the 2021/2022 academic year are included in the high category with a percentage of 69.21%.IDPenelitian ini bertujuan untuk mengetahui kesulitan belajar daring pada mata pelajaran biologi siswa kelas XI SMAN 2 Mandau. Penelitian ini dilaksanakn pada bulan Januari-Maret 2022. Pelaksanaan penelitian ini menggunakan metode deskriptif dengan teknik survei pada siswa kelas XI SMAN 2 Mandau  Tahun Ajaran 2021/2022. Teknik pengambilan sampel menggunakan teknik sampling secara acak (simple random sampling). Jumlah sampel penelitian adalah 122 siswa. Instrumen pada penelitian yang digunakan berupa angket kesulitan belajar daring yang terdiri dari 30 item pernyataan dan telah divalidasi. Teknik pengumpulan data pada penelitian menggunakan angket yang di sebarkan secara langsung di dalam kelas. Berdasarkan penelitian didapatkan hasil bahwa faktor penyebab kesulitan belajar daring pada mata pelajaran biologi siswa kelas XI adalah indikator pertama kendala teknis signal dan ketidakmampuan belajar daring 70,76% kategori kuat, indikator kedua pelaksanaan interaksi, tugas, dan bahan ajar dalam belajar daring 67,33% kategori kuat, indikator ketiga stake holder membantu pemerintah, sekolah, wali murid dalam belajar daring 69,55% kategori kuat. Berdasarkan hasil penelitian disimpulkan bahwa kesulitan belajar daring pada mata pelajaran biologi siswa kelas XI SMAN 2 Mandau Tahun Ajaran 2021/2022 memiliki nilai rata-rata persentase sebesar 69,21% dikategorikan kuat.